Indicadores de Degradação Ambiental / Desertificação no Município de Parambu - CE - Araújo, Diego Teixeira de (2016)
The desertification process is gradually increasing over the years in several municipalities in the Brazilian semiarid region. Several efforts have been made to diagnose these areas and look for the best ways to mitigate this problem. This research was developed in Parambu- CE, located in the southwestern region of the state of Ceará, in the peripheral region to the core of desertification Inhamuns. The general objective was to perform a partitioning of environmental systems in the municipality of Parambu, establishing, through indicators, the degree of susceptibility to environmental degradation / desertification of various compartments found. To conduct the survey, the method used was the integrated environmental analysis in the light of geosystemic and ecodynamics theories. Thus, sector and integrated environmental studies were conducted in order to delimit, by biogeophysical indicators (IGBDs), indexes of susceptibility to environmental degradation rates / desertification, on the studied environment. According to the methodology adopted, eight environmental systems were defined, namely: Hinterland Cana Brava; Hinterland Puiu; Hinterland of Cococi; Riverine Plain; Reverse Instant Plateau Ibiapaba; Reverse Dry Plateau Ibiapaba; Ridges Residuals and Inselbergs Groupings; Trays and Interior. The environmental system Ridges Waste and Inselbergs Groupings, showed a susceptibility index to environmental degradation / desertification very high; the Hinterland Puiu showed high susceptibility; Hinterland Cana Brava showed moderate susceptibility; the Hinterland of Cococi, low; Reverse Immediate and the Reverso Seco Ibiapaba Plateau presented both very low susceptibility.